A Case of Early Disseminated Neurological Lyme Disease Followed by Atypical Cutaneous Manifestations - Vamsi Kantamaneni; Vikas Sunder; Mohammad Bilal; Scott Vargo (Case Reports in Infectious Diseases)
Lyme disease (LD) is a tick-borne illness caused by Borrelia burgdorferi sensu stricto. An 80-year-old female from Pennsylvania, USA, presented to an outside hospital with fever, confusion, lower extremity weakness, and stool incontinence. CT head and MRI spine were unremarkable. An infectious work-up including lumbar puncture was negative. She was transferred to our tertiary care hospital. Patient was noted to have mild unilateral right-sided facial droop and a diffuse macular rash throughout the body. She denied any outdoor activities, tick bites, or previous rash. Intravenous ceftriaxone was started for suspected LD. The patient’s symptoms including facial droop resolved within 24 hours of antibiotic therapy. Polymerase chain reaction of the blood, IgM ELISA, and IgM Western blot testing for LD came back positive a few days after initiation of therapy. She was treated for a total of 21 days for neurological LD with complete symptom resolution. Not all patients have the classic “targetoid” EM rash on initial presentation, rash could develop after neurological manifestations, and prompt initiation of antibiotics without awaiting serology is paramount to making a quick and a full recovery. There should be a high index of suspicion for early disseminated LD, as presentations can be atypical.